Variations in IL-23 and IL-25 receptor gene structure, sequence and expression associated with the two disease forms of sheep paratuberculosis. (December 2016) - Nicol, Louise; Gossner, Anton; Watkins, Craig; Chianini, Francesca; Dalziel, Robert; Hopkins, John
Abstract The immunopathology of paucibacillary and multibacillary sheep paratuberculosis is characterized by inflammatory T cell and macrophage responses respectively. IL-23 and IL-25 are key to the development of these responses by interaction with their complex receptors, IL-23R/IL-12RB1 and IL-17RA/IL-17RB. In humans, variations in structure, sequence and/or expression of these genes have been implicated in the different pathological forms of tuberculosis and leprosy, and in gastrointestinal inflammatory disorders such as Crohn's disease. Sequencing has identified multiple transcript variants of sheepIL23R, IL12RB1 andIL17RB and a singleIL17RA transcript. RT-qPCR assays were developed for all the identified variants and used to compare expression in the ileo-caecal lymph node of sheep with paucibacillary or multibacillary paratuberculosis and uninfected animals. With IL-23 receptor, only theIL12RB1v3 variant, which lacks the receptor activation motif was differentially expressed and was significantly increased in multibacillary disease; this may contribute to high Th2 responses. Of theIL17RB variants only full lengthIL17RB was differentially expressed and was significantly increased in multibacillary pathology; which may also contribute to Th2 polarization.IL17RA expression was significantly increased in paucibacillary disease. The contrast between theIL17RA andIL17RB results may indicate that, in addition to Th1 cells, Th17 T cells are also involved in paucibacillary pathology.